LANGUAGE POLITENESS: APPLYING MADURESE CULTURE ROLE PLAY TO HABITUATE STUDENTS’ LANGUAGE MODESTY - Al Rosyiidah, Afiifah; Hikmah, Darul (Journal of Language and Literature, 2021)
This study aims to discover and explain how politeness maxims are employed in the Madurese theme role-playing. The study employs qualitative design of the research. It also employs observation technique and depth interview to obtain the data. In analyzing the data, it applies interactive model: data reduction, display, and/claim. This study finds ten politeness maxims in the using of Madurese theme role- playing.